Childhood poverty and evidence-based policy engagement in Ethiopia - Jones, N; Tefera, B; Woldehanna, T (Routledge, 2008)
This paper explores efforts to bridge multi-disciplinary research and policy engagement to tackle childhood poverty in developing country contexts, based on the experiences of Young Lives, an international longitudinal policy research project. It focuses on a case study involving the utilisation of research evidence on childhood poverty to shape policy debates about Ethiopia’s second generation Poverty Reduction Strategy Paper (2006-10). The discussion is situated within theoretical literature on the knowledge/policy/practice interface which supports the reconceptualisation of policy making as a non-linear dynamic process. It pays particular attention to the importance of understanding the political and policy contexts of Southern countries rather than simply importing Northern-derived models of advocacy. It concludes by teasing out generalisable lessons for translating research into social policy change.